Ammonium chloride reduces excitatory synaptic transmission onto CA1 pyramidal neurons of mouse organotypic slice cultures - Kleidonas, Dimitrios; Hilfiger, Louis; Lenz, Maximilian; Häussinger, Dieter; Vlachos, Andreas (Frontiers in Cellular Neuroscience, 2024)
Acute liver dysfunction commonly leads to rapid increases in ammonia concentrations in both the serum and the cerebrospinal fluid. These elevations primarily affect brain astrocytes, causing modifications in their structure and function. However, its impact on neurons is not yet fully understood. In this study, we investigated the impact of elevated ammonium chloride levels (NH4Cl, 5 mM) on synaptic transmission onto CA1 pyramidal neurons in mouse organotypic entorhino-hippocampal tissue cultures. We found that acute exposure to NH4Cl reversibly reduced excitatory synaptic transmission and affected CA3-CA1 synapses. Notably, NH4Cl modified astrocytic, but not CA1 pyramidal neuron, passive intrinsic properties. To further explore the role of astrocytes in NH4Cl-induced attenuation of synaptic transmission, we used methionine sulfoximine to target glutamine synthetase, a key astrocytic enzyme for ammonia clearance in the central nervous system. Inhibition of glutamine synthetase effectively prevented the downregulation of excitatory synaptic activity, underscoring the significant role of astrocytes in adjusting excitatory synapses during acute ammonia elevation.